Analisis lingkungan internal dan eksternal dalam perumusan strategi asuransi syariah di indonesia - PUTERI, NISRINA RANIA (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the influence of internal and external environments on strategic formulation in Islamic financial institutions, particularly in Indonesia’s Islamic insurance industry. The analysis applies a theoretical approach that integrates classical strategic management concepts with current developments in the sector. Internal factors include human resources, organizational structure, operational efficiency, and product innovation, while external factors comprise macroeconomic conditions, government policies, industrial competition, and changing Muslim consumer behavior. This study draws upon open-access literature, including three publications from UIN Maliki Malang and several recent studies on competitive strategies in Islamic finance. The findings reveal that a comprehensive understanding of internal strengths and weaknesses as well as external opportunities and threats critically determines the effectiveness of formulated strategies. The study highlights the importance of synergy between innovation, Sharia compliance, and environmental adaptation in building sustainable competitive advantage for Islamic insurance institutions.